Improving Employee Retention Based on Job Satisfaction in Human Resources at PT. BPR Restu Artha Makmur, Semarang City - Arel Dela Oktareka; Mutamimah Mutamimah (Komunitas Dosen Indonesia, 2025)
This study aims to analyze the influence of career development and reward systems on employee retention with job satisfaction as a mediating variable at PT BPR Restu Artha Makmur, Semarang City. Using quantitative analysis methods with PLS-SEM on 65 respondents, the results of the study showed that career development had a significant positive effect on job satisfaction (0.480; t=4.478; p=0.000) and employee retention (0.417; t=3.400; p=0.001), while the reward system had a significant effect on job satisfaction (0.477; t=5.411; p=0.000) but a significant negative effect on employee retention (–0.282; t=1.992; p=0.046). In addition, job satisfaction had a significant positive effect on employee retention (0.478; t=3.139; p=0.002). Mediation testing shows that career development (0.229; t=2.500; p=0.012) and reward systems (0.228; t=2.722; p=0.007) have a significant indirect effect on employee retention through job satisfaction. The Q² test also shows a strong predictive relevance for job satisfaction (0.661) and quite strong for employee retention (0.349), so this study emphasizes the importance of career development, fair reward systems, and increasing job satisfaction as key strategies in strengthening employee retention.